O papel da escola na promoção da alimentação saudável e seus impactos no aprendizado - (:unkn) unknown (ISB - Instituto de Saúde e Biotecnologia (Coari), 2026)
The school is a place of interactivity, seeking through systematic teaching to stimulate the competencies and skills necessary for the student to be the protagonist of their own learning, and especially of their rights and responsibilities. This project aimed to analyze how the school contributes to the promotion of healthy eating habits and how these practices impact students' learning. To achieve the proposed objectives, bibliographic research was used as a methodological resource, which is essential to support the questions raised. The research technique employed was narrative review. As an auxiliary tool, the studies were examined in terms of: the age group of the participants, the location of the research, the duration of the intervention conducted, and the type and period of monitoring of the eating habit. The results found showed that children and/or adolescents had better eating habits in studies that implemented a healthy eating intervention for a longer period, rather than through sporadic nutritional education activities. Ensuring that everyone in the school context can learn about healthy eating is a right established by law in Brazil. As final considerations, studies that demonstrate effective ways of food and nutrition education positively influencing healthy eating habits in basic education are important.
Keywords: Alimentação saudável infantil; Alimentação escolar; Hábitos alimentares escolares; Desempenho escolar; Healthy child nutrition; School feeding; School eating habits; School performance; CIENCIAS DA SAUDE: NUTRICAO; .; .; .